Could Primary Chemoradiotherapy in T2 Glottic Cancers Yield Results Comparable to Primary Radiotherapy in T1? Considerations from 531 German Early Stage Patients - Dyckhoff, Gerhard (Cancers (Basel), 2021)
SIMPLE SUMMARY: T1 laryngeal carcinoma arising from the vocal cords (glottis) is a highly curable disease with local control (LC) rates of over 90% by either primary radiotherapy (pRT) or transoral laser microsurgery (TLM). For slightly larger glottic tumors (T2), the outcome is significantly poorer. However, in the case of recurrent tumor after pRT, to save the patient’s life, the larynx has often to be removed (total laryngectomy). A remedy could bring more effective radiotherapy. In a large observational study on laryngeal cancer, a small number of early-stage patients received chemotherapy in addition to primary radiotherapy (pCRT). After pCRT, more patients could be saved from a recurrent tumor, lived markedly longer, and could preserve their functional larynx. pCRT can cause more side effects. However, according to the literature, for early-stage laryngeal cancer, they should be well controllable. To prove the increased effectiveness and acceptable toxicity, studies with more patients need to be conducted. ABSTRACT: T1 glottic cancer is a highly treatable disease with local control (LC) rates over 90% by either primary radiotherapy (pRT) or transoral laser microsurgery (TLM). LC of T2 glottic cancers is 15 percent points poorer on average. However, salvage after pRT entails more than 50% total laryngectomy. Therefore, there is a need for enhanced LC. Altered fractionation regimens improved LC in T1 but not in T2. For this reason, for T2, alternative strategies must be considered. In a large observational cohort study including 531 early-stage laryngeal cancers, a small number of patients were treated with primary chemoradiotherapy (pCRT). In multivariable analysis, factors associated with significantly poorer outcomes included age, comorbidities, supraglottic localization, and T category. While there was a significant difference between pRT and surgery (HR 1.79; 95%-CI: 1.15–2.79), there was none between pCRT and surgery (HR 0.70; 95%-CI: 0.33–1.51). There is evidence from the literature that pCRT in early glottic cancers could yield results that surpass the limits so far experienced in radiotherapy alone with acceptable toxicity. Thus, prospective randomized studies with larger numbers of patients are warranted.